Development of a synchronisation and video conversion unit for Denel Overberg Test Range's tracking radar - Uprety, Kushal (Department of Electrical Engineering, 2018)
This dissertation discusses the re-development of a subsystem of the tracking radar (TR) at Denel Overberg Test Range (OTR), defined as the Synchronisation and Video Conversion Unit (SVCU). The SVCU performs the task of baseband video processing, generation of all synchronisation triggers, and timing within the TR. The report is based on the Research and Design (R&D) project conducted at Denel OTR and built on the previous study where an SVCU model was designed and tested in SystemVue. A comprehensive measurement and analysis of all functions was first conducted on all (identical) TRs of Denel OTR to verify against the limited literature that is available relating to the SVCU. Various anomalies were discovered between the design specification documents and measured values. Modifications made to functions in the SVCU as a result of development done on other subunits of the TR and not documented were also discovered. A comprehensively revised design specification and high-level description for the SVCU was then generated. A new SVCU architecture was specified to improve the current tasks performed by various discrete analogue and digital components, Single-Board Microcontroller and data bus interfaces using commercial off the shelf (COTS) hardware. A prototype was built on the National Instruments (NI) PCI eXtensions for Instrumentation Express (PXIe) platform, utilising high-speed ADCs and Field Programmable Gate Array (FPGA) modules. All functions of the SVCU were modelled and implemented on these modules using LabVIEW and LabVIEW FPGA software. Fractional Decimators were designed to meet the sample resolution requirement of the range gates (used for range and Doppler measurement). Custom functions were written to integrate samples to increase SNR and apply a correction for errors carried over during the I/Q demodulation. The jitter on the synchronisation pulse responsible for RF energy transmission (TX), the ADC sample clock, and triggers signals that need to travel over excessively long transmission lines used for calibration were found to be the most critical aspects of the SVCU. The rootsum- square of all the jitter on these synchronisation pulses was calculated to ensure that the specified measurement accuracy of the TR is satisfied. Based on these findings, the PXIe based SVCU is recommended for deployment. Further development of other subunits for the TR receiver on the current platform is recommended, and an outline for future work is provided.